Hero & Exile : Art of Old English Poetry. - Greenfield, Stanley B. (Continuum International Pub. Group, 1989)
After a distinguished career as a teacher, scholar, bibliographer and literary critic, Stanley Brian Greenfield, Professor of English at the University of Oregon, one of the founders of the annual Anglo-Saxon England and of the International Society of Anglo-Saxonists, died in 1987. He wrote primarily on Anglo-Saxon topics as well as later English poetry. He deeply explored the Old English poetic corpus, pointing out important meanings and qualities in insightful and sensitive readings. Hero and Exile brings together some of his most important essays, divided into three sections - Beowulfian S.